THE DETERMINANT OF DECOMPOSITION OF FOREIGN DEBT IN INDONESIA - Diniah Islami; Mahrus Lutfi Adi Kurniawan (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
Since 1990 there have been reforms in both monetary policy and fiscal policy in Indonesia, which can affect the decomposition of foreign debt. The World Bank report in international debt statistics 2021 shows that Indonesia is one of the countries that have the most debt, which ranks 7th in the world and first in ASEAN with total foreign debt. This study uses time-series data from 1990 to 2021 using the VAR method to determine the response of foreign debt to macroeconomic fluctuations. Based on the results of the study shocks to the GDP variable will be responded to negatively by debt. The sensitivity of the debt response is shown to be positive when there are shocks to government spending and interest rates. The results of the variance decomposition show that government spending has the largest contribution to variability compared to other variables in the model. The implications of the research need to be careful in adding new debt amid uncertain macroeconomic conditions because it can burden the state budget